Crítica a la centralidad teórica-metodológica para explicar el desarrollo: una propuesta alternativa para el análisis de las políticas sociales = Critical perspectiva to the theorical and metodological centrality explaim the development: an alternative approach to social policy analysis - Ramírez, Liberio Victorino (Textos & Contextos (Porto Alegre))
To explain the development ideas and argue the changes in social policies in the XXI century as strategies to question the social policies in general and public education in particular, should ask the following question: How to move towards a new way of generating and appropriation of knowledge that doesn’t divide the reality as a research object and can be conceived with a constructivist approach than the unique thought? This article compares two paradigms or worldviews: neo evolutionary and constructivist. In this second is developing a proposal to adapt and reinterpret the new social policies in Latin America, especially the scientific policies oriented towards the generation and appropriation of knowledge